2017
DOI: 10.1039/c7fo00375g
|View full text |Cite
|
Sign up to set email alerts
|

β-Sitosterol and stigmasterol ameliorate dextran sulfate sodium-induced colitis in mice fed a high fat Western-style diet

Abstract: Phytosterols, the plant analogues of cholesterol, widely occur in the human diet. In this study, we investigated and compared the effects of stigmasterol and β-sitosterol (both with purities ≥ 95%) on dextran sulfate sodium (DSS)-induced colitis in C57BL/6J male mice fed a high fat western-style diet. Mice treated with DSS developed severe mucosal colitis, with a marked distortion and crypt loss of colonic surface epithelium. Both β-sitosterol and stigmasterol significantly inhibited colon shortening, lowered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 36 publications
1
53
0
Order By: Relevance
“…Some of those compounds have been proved to exhibit potent pharmacological effects. For example, stigmasterol (OB = 43.83, DL = 0.76) and kaempferol (OB = 41.88, DL = 0.24) can suppress inflammation of dextran sulfate sodium-induced colitis 23 , 24 , β -sitosterol (OB = 36.91, DL = 0.75) could inhibit TNBS-induced colitis 25 . It should be noted that Renshen contains a large amount of ginsenosides, and most of them did not meet the criteria of OB ≥30% and DL ≥0.18.…”
Section: Resultsmentioning
confidence: 99%
“…Some of those compounds have been proved to exhibit potent pharmacological effects. For example, stigmasterol (OB = 43.83, DL = 0.76) and kaempferol (OB = 41.88, DL = 0.24) can suppress inflammation of dextran sulfate sodium-induced colitis 23 , 24 , β -sitosterol (OB = 36.91, DL = 0.75) could inhibit TNBS-induced colitis 25 . It should be noted that Renshen contains a large amount of ginsenosides, and most of them did not meet the criteria of OB ≥30% and DL ≥0.18.…”
Section: Resultsmentioning
confidence: 99%
“…Formononetin, the most significant component in CSCC, is a natural isoflavone found in many Chinese medicinal herbs, such as SFR, and could offer protection against acute colitis in DSS-induced mouse models through the inhibition of cellular signaling cytokines produced by T cells in intestinal inflammation [43,44]. Licochalcone A obtained from LR attenuate DSS-induced colitis through the inhibition of NF-κB, a key factor in the increase in the number of 17 cells, and of IL-17 signaling [45,46]. Several results provide vital evidence to support the conclusion of C-T network analysis and suggest a potential mechanism underlying the effects of CSCC treatment on UC.…”
Section: Discussionmentioning
confidence: 99%
“…Stigmasterol and β-sitosterol had inhibitory effects on colitis induced by dextran sodium sulfate in C57BL/6J male mice. They critically suppressed colon shortening, colitis, and distal colon via the inactivation of NF-κB and decreased fecal hemoglobin content ( Feng et al, 2017 ). A recent study showed that β-sitosterol had an anti-inflammatory activity based on the rat pleurisy assay and rat paw edema test ( Paniagua-Pérez et al, 2017 ).…”
Section: Pharmacologymentioning
confidence: 99%